STAPHYLOCOCCUS AUREUS CONTAMINANT OF MEAT BASED FOOD STREET ON SALE ARROUND ELEMENTARY SCHOOL - Sri Handayani (UPT Penerbitan Universitas Jember, 2017)
Background: Eating is needed by body to gain enough nutritions for our life, recovery, energy at doing activities, growth and development. Nutritious foods are important for students in order to improve the quality of human resources. Applicable intervention to provide nutritious foods for them is by giving attention to their snacks. Snacks for students may give high contribution at providing nutritions for them, on the other hand snacks may also have a high-risk of biologically or chemically contaminated which lead them to have health problems. Methods: The research method was comparative used cross sectional study. The research measured Staphylococcus aureus contaminant of food street, behaviour of merchant, tableware and food presentation. The sampling method was purposive sampling by taking samples from different merchants. The samples size were 21 samples consisting of cilok, sausage and nuggets. Methods of data collection was interview, observation and laboratory examination. Results: The results showed : cilok, sausage, and nugget were contaminated by staphylococcus aureus with the percentage of 100%, 70% and 88% respectively. The unhygienic behavior of the merchants, tableware and food serving created a high risk of food contamination. Conclusions: factors which related to the contamination of Staphylococcus aureus in cilok, sausage, and nugget were the behavior of the merchants, tableware, and food serving. Keywords: Staphylococcus aureus, meat based street food, contaminant